Comparison of Industrially Relevant Fischer–Tropsch Cobalt Catalysts Supported on Alumina and Modified Silica with Complementary In-Situ and Operando Characterization Methods - Zimina, Anna; Fadlalla, Mohamed I.; Potgieter, Jana; Jimenez, Catalina E.; Ilica, Rabia; Sireci, Enrico; Sharapa, Dmitry I.; de Oliveira, Dominic; Hsu, Cherie; Saraci, Erisa; Wolf, Moritz; Sakoglu, Pinar; et al. (Journal of Physical Chemistry C, 2026)
Power-to-liquid processes are considered a crucial route to substitute petroleum-based processes for the production of valuable chemicals and liquid fuels, opening the possibility for the production of sustainable aviation fuels. Two selected catalysts, 20wt.%Co/Al2O3 (CA) and 20wt.%Co/TiO2–SiO2 (CTS), were tested in the Fischer–Tropsch synthesis (FTS) reaction under industrially relevant conditions. The CTS catalyst showed 10% higher activity, improved C5+ selectivity, and lower methane formation than the CA catalyst. The components of these complex catalysts were characterized, and the structural evolution of cobalt during activation and reaction was monitored by various in-situ and operando methods. H2 temperature-programmed reduction, X-ray diffraction, magnetometry, and X-ray absorption spectroscopy revealed a decrease in the temperature of stepwise cobalt reduction in CTS catalysts compared to CA. The reduction behavior of Co during activation was dependent on the support nature and strength of the metal–support interaction. The formation of composites with the support was proposed based on the results obtained by bulk probing XAS and more surface-sensitive NEXAFS methods. XRD, magnetometry, and XAS revealed that the size of the activated Co particles was dependent on the support chosen. The DFT modeling results confirmed the higher affinity of cobalt for titania, which might explain the smaller Co crystallite size and higher stability observed for the CTS catalyst. The difference in activity between the two commercially relevant cobalt-based catalysts on different supports could be linked to the difference in pore sizes and the strength of the metal–support interaction.
CRIS-Team Scopus Importer:2026-03-20